2022
DOI: 10.1038/s41598-022-17949-8
|View full text |Cite
|
Sign up to set email alerts
|

Selective removal of some heavy metals from Lanthanide solution by graphene oxide functionalized with sodium citrate

Abstract: Lanthanides are widely used in several advanced technologies, and the presence of heavy metal ions as traces reduce their efficiencies. Hence, adsorption of some heavy metals from Lanthanides aqueous solution using previously prepared graphene oxide-citrate (GO-C) composite was reported. In this regard, the GO-C was applied to remove various heavy metal ions (Fe, Ni, Mn) through the batch technique. The GO-C after the adsorption process was characterized by various advanced techniques. The results obtained fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…From the following relationship, the distribution coefficient ( K d ) of metal ions between the aqueous phase and the magnetic nanoparticle phase is calculated (Abu Elgoud et al 2022a ): Where V is the volume (L) and m is the weight (g) of the tungstate-modified magnetic nanoparticle; C o and C e are the initial and equilibrium concentrations (mg L −1 ) of Mo(VI), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…From the following relationship, the distribution coefficient ( K d ) of metal ions between the aqueous phase and the magnetic nanoparticle phase is calculated (Abu Elgoud et al 2022a ): Where V is the volume (L) and m is the weight (g) of the tungstate-modified magnetic nanoparticle; C o and C e are the initial and equilibrium concentrations (mg L −1 ) of Mo(VI), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…In this contribution, we set out to prove that the mathematical form of the FH isotherm as used in water contaminant adsorption research is fallacious because it has been inappropriately linearized. This erroneous form of the FH isotherm can be found in all the articles listed in Table as well as the reviews cited above. Furthermore, we draw attention to another fallacy concerning the use of faulty equilibrium constants derived from the linearized FH isotherm to calculate the Gibbs free energy change.…”
Section: Introductionmentioning
confidence: 97%
“…Since the mid-2000s, many studies have reported the modeling of water contaminant adsorption by means of the FH isotherm. Table presents a selection of such studies published across a broad spectrum of scholarly journals. As can be seen in Table , the experimental isotherms of numerous water contaminants, ranging from toxic metals to organic compounds, have been described by the FH isotherm. The inclusion of the FH isotherm in several reviews has no doubt promoted its use in this field of research. …”
Section: Introductionmentioning
confidence: 99%